2023
DOI: 10.7717/peerj.15757
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology for the mixed fungal fermentation of Codonopsis pilosula straw using Trichoderma reesei and Coprinus comatus

Abstract: The objective of this study was to investigate the cellulose degradation rate (CDR) and lignin degradation rate (LDR) of Codonopsis pilosula straw (CPS) and the optimal fermentation parameters for mixed fungal fermentation. Single-factor tests were used to study the effects of the fungal ratio (Trichoderma reesei: Coprinus comatus), fungal inoculum, corn flour content, and fermentation time on the degradation rate of cellulose and lignin. Based on the results of this experiment, the optimal fermentation factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“… Datsomor et al (2022) reported that the P. ostreatus treated straw had a lower lignin content (3.3%) compared to the P. chrysosporium (6.2%) with the raw straw recording the 8.2% lignin fraction. Wei et al (2023) reported that under the optimal parameters for fungal fermentation of Codonopsis pilosula straw, the cellulose degradation rate and lignin degradation rate reached 13.65 and 10.73%, respectively. These reports are consistent with our research results, proving that cellulose, hemicellulose and lignin in distillers grains can be degraded by microorganisms into simple sugars such as glucose and xylose.…”
Section: Discussionmentioning
confidence: 99%
“… Datsomor et al (2022) reported that the P. ostreatus treated straw had a lower lignin content (3.3%) compared to the P. chrysosporium (6.2%) with the raw straw recording the 8.2% lignin fraction. Wei et al (2023) reported that under the optimal parameters for fungal fermentation of Codonopsis pilosula straw, the cellulose degradation rate and lignin degradation rate reached 13.65 and 10.73%, respectively. These reports are consistent with our research results, proving that cellulose, hemicellulose and lignin in distillers grains can be degraded by microorganisms into simple sugars such as glucose and xylose.…”
Section: Discussionmentioning
confidence: 99%